Nitrogen cycling in an Antarctic ecosystem. 1. Biological nitrogen fixation in the vicinity of Syowa Station - Nakatsubo, Takayuki; Ino, Yoshio (1986)
P(論文) As part of the studies of the nitrogen flows in the Antarctic terrestrial ecosystems, nitrogen-fixing activities of moss communities, algae and lichens, collected in various ice-free areas near Syowa Station, East Antarctica, were measured by the acetylene reduction method. Moss communities which grew on the sand at dry habitats had dense cover of cyanobacteria and showed high nitrogen-fixing activities, while those at wet habitats near streams showed weak or no activity. Folious colonies of Nostoc sp. Showed significant activities. Some colonies of Chlorophyceae Prasiola crispa had weak activities which were probably due to associating cyanobacteria. No activity was detected for lichen species tested. The results suggest that nitrogen fixation by cyanobacteria, especially those epiphytic on mosses, plays an important role in the nitrogen budgets of terrestrial ecosystems developed in dry ice-free areas near Syowa Station. departmental bulletin paper